Individualism and the field viewpoint: cultural influences on memory perspective. - Martin, M; Jones, G (2012)
Two perspectives from which memories can be retrieved have been distinguished: field resembles the view from the first-person vantage point of original experience, whereas observer resembles the view from the third-person vantage point of a spectator. There is evidence that the incidences of the two types of perspective differ between at least two different cultural groups. It is hypothesised here that this is a special case of a more general relation between memory perspective and cultural individualism, such that field and observer perspectives are more prevalent among people from, respectively, relatively individualist and relatively collectivist societies. Memory perspectives adopted by participants from a range of different countries were recorded, and were found to vary in the predicted manner. Regression analysis showed that the potential effects of three other cultural variables - uncertainty avoidance, masculinity and, to a lesser extent, power distance - were eclipsed by the influence of individualism, and the implications are discussed.